2016
DOI: 10.1055/s-0042-114045
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatische und depressive Symptomatik bei Asylsuchenden

Abstract: Currently, there is a large number of refugees that are coming to Germany from (civil) war zones. The aim of this study was to estimate the extent of posttraumatic stress and depressive symptoms amongst asylum seekers in Germany. In the summer of 2015, 280 adult refugees (88,2% men) were interviewed with the support of translators in the Lower Saxony State Refugee Reception Center, Brunswick. Data was categorized due to country of origin (Balkan States, Middle East, Northern Africa, Rest of Africa). The Posttr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
4
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 11 publications
0
16
4
1
Order By: Relevance
“…Approximately one-third of the participants met the criteria for at least one diagnosis. These results are in contrast to the findings of previous studies from different countries that have shown high prevalence rates of mental distress among Syrian refugees (713). …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Approximately one-third of the participants met the criteria for at least one diagnosis. These results are in contrast to the findings of previous studies from different countries that have shown high prevalence rates of mental distress among Syrian refugees (713). …”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have investigated the mental health problems of Syrian refugees in recent years. Prevalence rates range from 20.5 to 35.7% for PTSD (712), from 20 to 43.9% for depression (79, 12, 13), and from 19.3 to 31.8% for anxiety (8, 12). …”
Section: Introductionmentioning
confidence: 99%
“…In comparison to other studies about refugees from Syria [12,13,14] and Iraq [15,16], we found consistent results. Compared to studies from Germany [17,18,19], we found similar or higher levels of mental distress.…”
Section: Discussioncontrasting
confidence: 52%
“…In general, the prevalence rates in the literature for depression in refugees vary between 3% and 47%, and for anxiety between 5% and 90% [4]. In studies in Germany, the prevalence rates for depression vary between 20% and 80% [10,17,18,19], and for anxiety between 19.3% and 80% [10,18]. In our sample, 57.1% of the asylum seekers endorsed symptoms of at least moderate depression and 39.3% for at least moderate anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation